1999
DOI: 10.1177/204748739900600413
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibrinogen as a Risk Factor for Restenosis after Percutaneous Transluminal Renal Angioplasty in Patients with Atherosclerotic Renal Artery Stenosis

Abstract: Background In contrast to those for coronary restenosis, the data regarding the risk factors for renal restenosis are limited.Objective To evaluate potential humoral risk factors for restenosis after percutaneous transluminal renal angioplasty (PTRA).Methods We studied 27 patients aged 54 ± 10 years with atherosclerotic renal artery stenosis in a 1-year prospective follow-up. Restenosis (confirmed by angiography) occurred in eight patients 1-6 months after PTRA. We detected no Doppler ultrasound evidence of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…These results are in keeping with an earlier study by Schillinger et al who investigated the levels of CRP and serum amyloid A (SAA) in connection with acute phase reactions [24]. They found that the level of these markers were significantly higher within 48 hours following intervention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in keeping with an earlier study by Schillinger et al who investigated the levels of CRP and serum amyloid A (SAA) in connection with acute phase reactions [24]. They found that the level of these markers were significantly higher within 48 hours following intervention.…”
Section: Discussionsupporting
confidence: 91%
“…Several earlier studies have been involved in investigating the possible role of hemorheological and hemostaseological changes in restenosis following endovascular intervention [7,8,[20][21][22][23][24][25][26]. In an earlier study of patients following PTCA we found that the RBC count, plasma viscosity and total blood viscosity decreased significantly within 30 minutes following intervention, the RBC count increased in conjunction with the total blood viscosity until the six month-follow up.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Later on, this association was confirmed in hypertensive patients with narrowing of a renal artery by 50% or more [44]. Furthermore, in 27 patients with ARAS fibrinogen levels were related to an increased rate of restenosis after 1 year of renal artery angioplasty [22]. Levels of homocysteine were reported to be higher in 58 patients with angiographic evidence of ARAS and impaired renal function than in normotensive subjects [23].…”
Section: Discussionmentioning
confidence: 65%
“…Among these conditions, elevated lipoprotein(a) levels and a prothrombotic state might be of particular interest because both have been shown to have specific relevance for the development of organ damage in hypertensive patients [19,20]. Previous studies have suggested a possible contribution to ARAS of plasma fibrinogen [21,22] and homocysteine [23] levels, whereas the role of lipoprotein(a) remains unclear [21,24,25], most likely because none of the studies conducted so far has been specifically designed to investigate its role. This study was designed to investigate whether plasma levels of lipoprotein(a) and hemostatic and fibrinolytic markers are associated with ARAS and can predict its presence in hypertensive patients.…”
Section: Introductionmentioning
confidence: 98%